Hugo Riemann and the birth of modern musical thought - Rehding, Alexander (New perspectives in music history and criticism, 2003)
By situating Riemann's musical thought within turn-of-the-century discourses about the natural sciences, German nationhood and modern technology, this book reconstructs the cultural context in which Riemann's ideas not only 'made sense' but advanced an understanding of the tonal tradition as both natural and German.